Effect of calcium vs. placebo on long-term outcomes in patients with out-of-hospital cardiac arrest. (October 2022) - Vallentin, Mikael Fink; Granfeldt, Asger; Meilandt, Carsten; Povlsen, Amalie Ling; Sindberg, Birthe; Holmberg, Mathias J.; Iversen, Bo Nees; Mærkedahl, Rikke; Mortensen, Lone Riis; Nyboe, Rasmus; Vandborg, Mads Partridge; Tarpgaard, Maren; et al.
Abstract: Objective: The Calcium for Out-of-hospital Cardiac Arrest (COCA) trial was a randomized, placebo-controlled, double-blind trial of calcium for out-of-hospital cardiac arrest. The primary and secondary outcomes have been reported previously. This article describes the long-term outcomes of the trial. Methods: Patients aged ≥18 years were included if they had a non-traumatic out-of-hospital cardiac arrest during which they received adrenaline. The trial drug consisted of calcium chloride (5 mmol) or saline placebo given after the first dose of adrenaline and again after the second dose of adrenaline for a maximum of two doses. This article presents pre-specified analyses of 6-month and 1-year outcomes for survival, survival with a favorable neurological outcome (modified Rankin Scale of 3 or less), and health-related quality of life. Results: A total of 391 patients were analyzed. At 1 year, 9 patients (4.7%) were alive in the calcium group while 18 (9.1%) were alive in the placebo group (risk ratio 0.51; 95% confidence interval 0.24, 1.09). At 1 year, 7 patients (3.6%) were alive with a favorable neurological outcome in the calcium group while 17 (8.6%) were alive with a favorable neurological outcome in the placebo group (risk ratio 0.42; 95% confidence interval 0.18, 0.97). Outcomes for health-related quality of life likewise suggested harm of calcium but results were imprecise with wide confidence intervals. Conclusions: Effect estimates remained constant over time suggesting harm of calcium but with wide confidence intervals. The results do not support calcium administration during out-of-hospital cardiac arrest. Trial registration: ClinicalTrials.gov -number, NCT04153435.